Watergate prosecutor - Merrill, William H. (Michigan State University Press, 2008)
This is the inside story of the Watergate trials. Written by the ultimate insider who helped change the course of history: William Merrill was the Special Prosecutor who sent the ""plumbers"" to jail. Not just any plumbers, but the ""Nixon plumbers, "" hired by the White House to ""stop leaks"" by any means necessary. Officially, they were the Special Investigation Unit. Unofficially, they were the ""dirty tricks squad, "" whose illegal actions eventually caused the President to resign his office. Bill Merrill prosecuted the plumbers. Here, more than thirty years late.